PENGARUH CORPORATE SOCIAL RESPONSIBILITY, POLITICAL CONNECTION, CAPITAL INTENSITY DAN INVENTORY INTENSITY TERHADAP TAX AGGRESSIVENESS - Muhammad Rinaldi; Novita Weningtyas Respati; Fatimah Fatimah (SIMAK, 2020)
This study examines the influence of Corporate Social Responsibility (CSR), Political Connection, Capital Intensity, Inventory Intensity of Tax Aggressiveness. Samples were selected using a purposive sampling method so as many as 33 companies in the Basic Industry and Chemical sectors as population, which are listed on the Indonesia Stock Exchange in the 2016-2018 period. The results of this study indicate that Capital Intensity positive affects on Tax Aggressiveness, which indicates that the higher the Capital Intensity, it is suspected that the company practices Tax Aggresiveness. The Corporate Social Responsibility and Political Connection variables show the resultys do not have a positive effect, which means that the higher the level of CSR disclosure and the companies that have Political Connection, the company allegedly did not practice Tax Aggresiveness. Inventory Intensity variable does not affect the Tax Aggressiveness which shows that the high or low value of Invetory Intensity does not affect the presence or absence of the company allededly practicing Tax Aggressiveness.